TEKNIK POLYA DALAM PENYELESAIAN MASALAH GEOMETRI - Rahma Wahyu (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
This study aims to analyze the steps for solving mathematical problems by students' understanding of the geometric material in story problems based on the Polya technique. This research was conducted in one of the Islamic elementary schools in Batu City on six students in grade 6. The approach taken is to use a descriptive qualitative approach. The research was carried out using triangulation methods, namely observing the problem-solving process, interviews, and reviewing documents (students' work). Interviews in this study were conducted with several students, namely two high ability people, two low ability people, and two medium ability people. The analysis was carried out by concluding the data obtained based on the observations that have been made. The study results showed that the Polya technique showed different results on the results of solving the problems of each category of students in solving story problems about the area of squares and rectangles. Based on these results, it can be seen that students' understanding of the geometry material on the story problem.